Singers, Heroes, and Gods in the "Odyssey" - Segal, Charles, 1936-2002 (Myth and poetics., 2019)
One of the special charms of the Odyssey, according to Charles Segal, is the way it transports readers to fascinating places. Yet despite the appeal of its narrative, the Odyssey is fully understood only when its style, design, and mythical patterns are taken into account as well. Bringing a new richness to interpretation of this epic, Segal looks closely at key forms of social and personal organization which Odysseus encounters in his voyages. Segal also considers such topics as the relationship between bard and audience, the implications of the Odyssey's self-consciousness about its own poetics, and Homer's treatment of the nature of poetry.